1990
DOI: 10.1111/j.1399-302x.1990.tb00409.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies of the outer membranes of Bacteroides gingivalis, strains ATCC 33277, W50, W83,381

Abstract: Outer membrane fractions from Bacteroides gingivalis strains ATCC 33277, 381, W50, and W83 were isolated by French pressure cell disruption and the distribution of major and minor proteins was determined by SDS-PAGE electrophoresis after treatment with 2% Sarkosyl and 2% Triton X-100. Heat-modifiability of the outer membrane proteins (OMPs) from these B. gingivalis strains was also determined after treatment at 100 degrees C and analysis by both 1- and 2-dimensional SDS-PAGE. The distribution of the OMPs on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 48 publications
3
30
0
Order By: Relevance
“…These studies also showed strong similarities between W83 and W50 but placed them in a different group from that of ATCC 33277 and 381. Evidence that the four strains may be independent comes from analyses of the protein compositions of their outer membranes, from which subtle differences could be observed (18).…”
Section: Discussionmentioning
confidence: 99%
“…These studies also showed strong similarities between W83 and W50 but placed them in a different group from that of ATCC 33277 and 381. Evidence that the four strains may be independent comes from analyses of the protein compositions of their outer membranes, from which subtle differences could be observed (18).…”
Section: Discussionmentioning
confidence: 99%
“…The pellet, designated the cell envelope fraction (CEF), was washed three times, resuspended in SB, and stored at 4°C. The outer membrane fraction (OMF) was prepared by 2% (wt/vol) N-lauryl sarcosinate treatment of the CEF for 1 h at room temperature with agitation (10,15). The insoluble OMF was pelleted by ultracentrifugation (as above), washed three times in CB, resuspended in SB, and stored at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…The treated membrane fractions were washed twice and then resuspended and stored in SB at 4°C. Protein concentrations were determined with the bicinchoninic acid assay (Pierce, Rockford, Ill.) with bovine serum albumin as a control (15).…”
Section: Methodsmentioning
confidence: 99%
“…Protein determination. Total protein content was determined by a modification of the bicinchoninic acid protein assay (Pierce, Rockford, Ill.) (23) with human SA as the standard.…”
Section: Methodsmentioning
confidence: 99%